Factors Assosiated With Hellp Syndrome On Severe Preeclampsi Dan Eclampsia In General Hospital Ulin Banjarmasin 2012-2013 - zakiah zakiah; vonny khresna dewi; Ahmad rizani (Politeknik Kementerian Kesehatan Banjarmasin, 2016)
Purpose: To know the factors that assosiated with HELLP syndrome on severe preeclampsi dan eclampsia in General Hospital Ulin banjarmasin 2012-2013. Methods: the research was analytical with cross sectional study. The sampel was parturient with preeclampsia and eclampsia in General Hospital Ulin Banjarmasin periode 2012-2013. The sampels selected through simple random samplingwith 100 respondent. Data analyzed with Chi Square test(α=0,05). Result: the prevalence of HELLP syndrome at General Hospital Ulin Banjarmasin was 24%, wich consisted 61,0% multipararous, 77,0% found at maternal age ≥ 25 years and with no delivery complication. There was no assosiation between parity, age, and historical delivery. Conclusion: prevalence of HELLP syndrome was 24%, most of the cases was found at maternal age ≥ 25 years.